'Wings' - Aeronautical Engineers newspaper, 1945 (1945)
1945 1939-1945 "'Wings' - Aeronautical Engineers newspaper, 1945" [HFR0085], 1945 Wings was the monthly bulletin of the Aeronautical Engineers Association, formed in 1943 to protect the interests of aircraft engineers who were regarded as 'dilutees' by the Amalgamated Engineering Union because they had no apprenticeship training. The AEA had a number of bitter disputes with other established aircraft industry unions.